Battle of belonging : on nationalism, patriotism, and what it means to be Indian - Tharoor, Shashi (New Delhi Aleph Book Company, 2020)
The Battle of Belonging There are over a billion Indians alive today. But are some Indians more Indian than others? To answer this Question, one that is central to the identity of every man, woman, and child who belongs to the modern Republic of India, eminent thinker and bestselling writer Shashi Tharoor explores hotly contested ideas of nationalism, patriotism, citizenship, and belonging. In the course of his study, he explains what nationalism is, and can be, reveals who is anti-national, what patriotism actually means, and explores the nature and future of Indian nationhood. He gives us a clear-sighted view of the forces working
Keywords: Nationalism - India; Hindutva - India